Auxin and the integration of environmental signals into plant root development - Kazan, Kemal (Oxford University Press, 2013)
BACKGROUND: Auxin is a versatile plant hormone with important roles in many essential physiological processes. In recent years, significant progress has been made towards understanding the roles of this hormone in plant growth and development. Recent evidence also points to a less well-known but equally important role for auxin as a mediator of environmental adaptation in plants. SCOPE: This review briefly discusses recent findings on how plants utilize auxin signalling and transport to modify their root system architecture when responding to diverse biotic and abiotic rhizosphere signals, including macro- and micro-nutrient starvation, cold and water stress, soil acidity, pathogenic and beneficial microbes, nematodes and neighbouring plants. Stress-responsive transcription factors and microRNAs that modulate auxin- and environment-mediated root development are also briefly highlighted. CONCLUSIONS: The auxin pathway constitutes an essential component of the plant's biotic and abiotic stress tolerance mechanisms. Further understanding of the specific roles that auxin plays in environmental adaptation can ultimately lead to the development of crops better adapted to stressful environments.